Desain Peremanjaan Fasilitas Tempat Parkir Objek Wisata Pantai Lebih dalam Upaya Meningkatkan Hospitality Pengunjung - I Kadek Merta Wijaya; Dewa Ayu Nyoman Sriastuti; I Ketut Sugihantara; Lilik Antarini (Jurnal Sutramas, 2024)
The beach has more appeal as a transit and culinary tourist attraction. Visitors who travel from Denpasar to Gianyar or Klungkung rest at Sangat Beach while enjoying seafood culinary delights. More Beach Culinary started from the feedback from fishermen on Plus Beach which was sold on the beach. Apart from that, More Beach is a place to carry out melasti for the people of More Village. The development of Morekebang Beach as a transit and culinary area has an impact on parking facilities which are inadequate in terms of the number and quality of parking spaces. This service activity aims to produce a master plan design for the arrangement of parking spaces that accommodates the needs for the number of vehicles, arrangement of vehicle types, and the quality of comfort for visitors who park their vehicles at Sangat Beach. This activity method is carried out in four stages, namely the problem mapping method, conceptual design proposal, induction in the form of a master plan arrangement drawing, and focus group discussion with the community/managers of the Pantai Sangat tourist attraction. The results of this activity are in the form of a master plan for rejuvenating parking facilities according to zoning regulations, planning shade trees, drainage and lighting utility networks, and driver rest areas.